Measurement of Impairment among Children with Attention Deficit Hyperactivity Disorder as Part of Evaluating Treatment Outcome - Ahmed M. Al-Ansari (Sultan Qaboos University Medical Journal, 2013)
Objectives: This study assesses the impairment and treatment outcome of children with attention deficit hyperactivity disorder (ADHD) in an outpatient child psychiatry clinic, using multiple sources, including the Children Global Assessment Scale (C-GAS). Methods: A total of 20 children, aged 4 to 16 years, were recruited serially in 2010 from the Child Psychiatric Unit of the Psychiatric Hospital, Manama, Bahrain. The children received a diagnosis of ADHD using the Diagnostic and Statistical Manual of Mental Disorders Text Revision (DSM-IV-TR). The children were assessed with the C-GAS by a blinded investigator, initially at the beginning of the treatment and then one year later. Results: The parents of the patients reported improvement in all cases; the improvement in impairment after one year, assessed using the C-GAS, was significant for all of the cases (P = 0.001) and low for those with comorbidity (P = 0.07). Conclusion: Measurement of improvement using the C-GAS was a suitable method of collecting data, and hence should be included in routine clinical practice for both ADHD diagnosis and outcome measurement.